Project-Based Learning Method to Enhance Students’ Digital Business Competence in English Course - Muzdalifah, Indah; Muhammad Zaim; Refnaldi; Lisnawita; Dina Fitriani; Firmansyah (International Journal of Language Pedagogy, 2024)
English is a compulsory subject studied in every study program. English is usually learned in the first and second semesters. This research aims to make English learning more enjoyable. This type of research is descriptive analysis. The instrument used is a questionnaire. The students involved in this research were 28 people from the digital business study program. This study found the correct type of project-based learning for students is role-playing by imitating conversations in English from a short video that is rich in moral values played by students and then made into a video. The second finding is that the results of the questionnaire as a research instrument concluded that the task of project learning was beneficial for them in understanding English learning.